Fungal Infections Masquerading as Gastrointestinal Tract Malignancies – A Series of Three Cases - Chaturvedi, Rachana Amit; Baste, Balaji D; Karegar, Manjusha M; Gupte, Prajakta A; Joshi, Amita S (Annals of Pathology and Laboratory Medicine, 2021)
Fungal infections of the gastrointestinal tract (GIT) are not rare, but get missed due to their misleading clinical features. Here we report three GIT fungal infections at different locations with varied symptoms. We received surgical resection specimens with the clinical suspicion of malignancy for all. The first was a case of Aspergillosis, at an uncommon site, esophageal, in a 60year diabetic male with a suspicion of carcinoma in view of presence of dysphagia and a stricture on CT. The second was a 60-year male, a case of stomach Zygomycosis with no definite immunosuppression, who presented with an intra-operative suspicion of malignancy, and showed fungal angio-invasion and ischemic perforation. Third was a 32year immunocompetent male, a case of GI histoplasmosis with an uncommon presentation, showing obstructive symptoms due to an ileocaecal mass with a clinical suspicion of TB/malignancy. Thus, a high index of suspicion for fungal a etiology in GIT is essential, because misdiagnosis can lead to a radical surgery. Timely treatment with appropriate antifungal therapy is crucial as high mortality is associated with certain fungi.